Prediction of battery depletion in implanted pacemakers. Issue 2 (March 1973) - Davies, Geoffrey; Siddons, Harold
Abstract : By the use of a measuring oscilloscope and the standard electrocardiogram limb leads the degree of battery depletion in an implanted pacemaker can be estimated. A formula based on readings obtained by this means has been used to determine when Devices fixed rate pacemakers should be removed. Laboratory tests show that 90% of their useful life is obtained by this means and it proved possible to extend the period of implantation from an arbitrary 24 months to 25 to 34 months without failure from battery depletion.